Acceptance and reverification testing for industrial computed tomography - a simulative study on geometrical misalignments - Wohlgemuth, Florian; Hausotte, Tino; Schmidt, Ingomar; Kimmig, Wolfgang; Imkamp, Karl Dietrich (Journal of Sensors and Sensor Systems, 2022)
Acceptance and reverification testing for industrial X-ray computed tomography (CT) is described in different standards (E DIN EN ISO 10360-11:2021-)4, 2021; VDI/VDE 2630 Blatt 1.3, 2011; ASME B89.4.232020, 2020). The characterisation and testing of CT system performance are often achieved with test artefacts containing spheres. This simulative study characterises the influence of different geometrical error sources - or geometrical misalignments - on these sphere measurements. The two measurands on which this study focuses are the sphere centre-to-centre distances and the sphere probing form errors.
CRIS-Team WoS Importer:2022-07-01